Age relationships and sex differences in serum levels of pregnenolone and 17-hydroxypregnenolone in healthy subjects - Hill, M; Lukác, D; Lapcík, O; Sulcová, J; Hampl, R; Pouzar, V; Stárka, L (Clinical chemistry and laboratory medicine, 1999)
17-Hydroxypregnenolone (3beta,17alpha-dihydroxypregn-5-en-20-one) and pregnenolone (3beta-hydroxypregn-5-en-20-one) were determined by radioimmunoassay following HPLC separation in serum of healthy subjects of both sexes from 2 to 66 years old (29 girls, 85 women, 30 boys, 89 men). The effects of age and sex on the levels of both steroids were investigated and the upper limits of normal in age groups were determined. The 17-hydroxypregnenolone levels as a function of age were characterized by a statistically significant maximum at the age of 18 and 20 years followed by a local minimum at the age of 39 and 37 years and by a statistically insignificant local maximum at the age of 55 and 49 years in men and women, respectively. Pregnenolone age-dependence was similar and the statistically significant maximum was reached at the age of 17 and 16 years, the local minimum occurred at the age of 37 and 38 years and the second, statistically insignificant, local maximum at the age of 48 and 47 years in men and women, respectively. Both 17-hydroxypregnenolone and pregnenolone in both sexes exhibited similarly shaped peaks with age. Both peaks of the polynomial fit in 17-hydroxypregnenolone were more pronounced in men than in women (13.0 and 9.20 nmol/l in the first peak; 7.72 and 4.78 in the second peak respectively). The situation with pregnenolone was the opposite. Both peaks of the polynomial fit in pregnenolone were lower in men than in women (2.29 and 3.21 nmol/l in the first peak; 0.92 and 1.78 in the second peak, respectively). The higher serum levels of pregnenolone at puberty and during fertile age and their wider variance in comparison with men could, be explained by the different gonadal steroidogenesis depending on the menstrual cycle, where the pregnenolone serves as a substrate for progesterone formation. The age dependencies of 17-hydroxypregnenolone and pregnenolone in women resembled that of unconjugated dehydroepiandrosterone. These results indicate that the increased metabolic activity in gonads in adolescence concerns not only dehydroepiandrosterone as the product of the 5-ene metabolic pathway but also its precursors.
Keywords: Sex Factors; Humans; lidé středního věku; dítě; Child; Female; Aged; dospělí; věkové faktory; senioři; lidé; pregnenolon; 17-alpha-Hydroxypregnenolone; časové faktory; sexuální faktory; předškolní dítě; Adult; ženské pohlaví; Male; Middle Aged; Adolescent; 17-alfa-hydroxypregnenolon; Age Factors; mužské pohlaví; Child, Preschool; Time Factors; Pregnenolone; mladiství